RESULTS OF A GNSS CAMPAIGN BETWEEN ISLA DEL COCO AND PACIFIC SEACOAST OF COSTA RICA AS INPUT FOR ESTIMATING DISPLACEMENT - Moya-Zamora, Jorge (2014)
This article presents the results of the quantification of the displacement of the Pacific coast of Costa Rica, materialized by seven points in the national geodetic network of first order and based on GNSS measurements carried out jointly by the Escuela de Topografía, Catastro y Geodesia (ETCG) de la Universidad Nacional, el Instituto Geográfico Nacional (IGN) y la Unidad Ejecutora de la Programa de Regularización de Catastro y Registro (UE). Measurements from Costa Rica were linked with two points about 550 km away from mainland Costa Rica, located properly in Cocos Island. The processing of the measurements and the subsequent adjustment was made by combining the online processing technique Precise Point Positioning and the use of commercial software Topcon Tools. Additionally exposed some technical details of the second season of Costa Rica SIRGAS, ISCO station located at Cocos Island.